FACTORS ASSOCIATED WITH MYOPIA AMONG SECONDARY SCHOOL STUDENTS IN HOANG MAI TOWN, NGHE AN PROVINCE (2020) (Vietnam Journal of Community Medicine, 2022)
Objectives: Untreated myopia is the leading cause of vision impairment in children. The study wasconducted in order to determine the prevalence and some factors associated with myopia in secondaryschool students in Hoang Mai town, Nghe An province.Methods: The study employed descriptive analytical research method with the study subjects ofsecondary school students in Hoang Mai town, Nghe An province.Results: The prevalence of myopia in secondary school students in Hoang Mai town was 14.2%,in which grade 8 and grade 9 students were at a higher risk of myopia than grade 6 with OR = 1.7(95%CI:1.2–2.5) and OR = 1.8 times (95%CI:1,2–2.6). Factors associated with myopia includednear vision distance < 30 cm, with OR = 5.2, 95%CI: 3.5 – 7.9, p < 0.01; eye rest after 30 minutes ofcontinuous near vision, with OR = 1.6, 95%CI: 1.1-2.5, p < 0.05; outdoor activity time < 14 hours/1week (OR= 1.77, 95%CI: 1.15 – 3.9, p < 0.05) and reading and writing at home ≥ 21 hours/1 week (OR = 1.5, 95% CI: 1.1- 2.1, p < 0.01).Conclusions: Near vision distance < 30 cm, continuous reading for 30 minutes without eye rest,outdoor activity time < 14 hours/week, and reading and writing > 21 hours/week were factorsassociated with myopia in the study subjects.
Keywords: Myopia, secondary school students, near vision, far vision.